2017
DOI: 10.1111/mam.12097
|View full text |Cite
|
Sign up to set email alerts
|

Bat boxes are not a silver bullet conservation tool

Abstract: Nest boxes are often promoted as substitute structures for hollow-dependent fauna, but are they generally effective? In a long-term bat-box monitoring project in south-eastern Australia, box occupancy was dominated by one common and widespread urban-adapted species, Gould's wattled bat Chalinolobus gouldii. In contrast, the 13 other bat species in the area made little or no use of the boxes. Policymakers, land managers and conservation professionals working in the field of biodiversity offsets should be aware … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 13 publications
0
44
0
Order By: Relevance
“…There is a growing body of evidence questioning the general efficacy of traditional timber or plywood nest boxes as a conservation tool for communities of hollow-dependent fauna in disturbed landscapes [4,21,25,71,110]. Combined with the preliminary evidence of the uptake and use of chainsaw hollows by wildlife [31,37,38], this provides a positive impetus for collaboration between policy makers, conservation practitioners, the arboriculture industry, and managers of biodiversity offset programs, to empirically test the effectiveness of mechanically creating artificial hollows to provide well-insulated permanent structures within trees for hollow-dependent fauna.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a growing body of evidence questioning the general efficacy of traditional timber or plywood nest boxes as a conservation tool for communities of hollow-dependent fauna in disturbed landscapes [4,21,25,71,110]. Combined with the preliminary evidence of the uptake and use of chainsaw hollows by wildlife [31,37,38], this provides a positive impetus for collaboration between policy makers, conservation practitioners, the arboriculture industry, and managers of biodiversity offset programs, to empirically test the effectiveness of mechanically creating artificial hollows to provide well-insulated permanent structures within trees for hollow-dependent fauna.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, better-insulated nest boxes may still be used predominantly by common, abundant species. For example, long-term monitoring of bat boxes in Melbourne, Australia has shown that, despite the provision of boxes constructed from materials with a range of insulative properties (ranging from 12 mm plywood to 90 mm pine), box use was dominated by one widespread, urban-adapted species, Gould's wattled bat Chalinolobus gouldii (Gray, 1841) [71]. Further research is required to investigate whether there is a link between the thermal profiles in nest boxes (compared to tree hollows) deployed in disturbed landscapes and their disproportionate level of use by widespread, highly adaptable species of birds [29,93,94] and mammals [21,71,95,96].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Occupancy of these bat boxes can be affected by canopy cover, box design, level of human disturbance, and adequate solar exposure (White, 2004, Rueegger et al, 2018. Moreover, not all species are likely to use bat boxes at equal frequencies (Griffiths et al, 2017). However, little attention has been given to more recent methods for either more affordable bat species identification or monitoring of deployed bat boxes using non-invasive smartphone technology.…”
mentioning
confidence: 99%